The effect of different cold water immersion protocols on recovery from exercise-induced muscle damage - Vieira, A.; Siqueira, A. F.; Ferreira-Junior, J. B.; da Cunha, E. C.; Durigan, J.; Carmo, J.; Blazevich, A.; Bottaro, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Cryotherapy is widely accepted as recovery strategy to accelerate muscle recovery from strenuous exercise. Cold water immersion (CWI) is one of the most popular cold modality. It has been suggested that the therapeutic effect of CWI begins with water at 15 °C, but it is also assumed that lower temperatures may provide better outcomes (Merrick et al. 2003; Wilcock et al. 2006). However, the optimal temperature of CWI on the time course of muscle damage recovery are still controversial. Therefore, the aim of this study was to compare the effects of CWI at 15ºC and CWI at 5ºC on recovery from exercise-induced muscle damage. Forty-five college students performed a damaging exercise (5x20 drop jumps) and they were randomly allocated into one of three groups: 1) CWI at 5ºC (G5, n=14), 2) CWI at 15ºC (G15, n=14) or 3) control (CG, n=14). Individuals from CWI groups had their lower limbs immerged in water for 20 min, whereas those from control group remained seated for the same period. Isometric strength, countermovement jump (CMJ) performance, delayed-onset muscle soreness (DOMS), and serum creatine kinase (CK) activity were measured before, immediately after, 24, 48, 72, 96 and 168 h post-exercise. There was no difference between groups for isometric strength recovery (p=0.73). However, both G5 and G15 groups had a quicker recovery in CMJ performance than control group (p<0.05). Furthermore, G15 recovered CMJ performance 72 h, whereas G5 recovered only 96 h after EIMD. The control group did not recover CMJ at any time point investigated. G15 also demonstrated no significantly difference on CK activity from baseline after 72 and 168 h post-exercise, whereas the CK from both G5 and GC remained higher than baseline throughout study`s period. There was a trend toward lower DOMS (p=0.06) in G15 when compared to the GC 24 h postexercise. CWI hastened CMJ performance recovery, but not the isometric strength recovery. This discrepancy suggest that CWI might enhance aspects of stretch-shortening cycle, such as: utilizing elastic energy of structures of the musculature, activating proprioceptive reflexes, increasing the time to produce force and/or by potentiating sarcomere length (Byrne et al. 2004; White et al. 2014). Furthermore, the groups demonstrated different time course recovery on CMJ. G15 recovered linearly, whereas both G5 and GC demonstrated a further decline in performance. This second drop in performance might be associated with a secondary damage as consequence of excessive inflammatory response (Byrne et al. 2004). In summary, the results of the present study suggest that independent of the temperature CWI may enhance muscle damage recovery. Also, it appears that 15 ºC may improve recovery from strenuous exercise when compared to lower temperatures.